Pharmacoeconomic Study on the Application of Magnetic Resonance Imaging with Gadoxetic Acid in Addition to Contrast-Enhanced Computed Tomography in Diagnosis of Hepatocellular Carcinoma - G. G. Kаrmаzаnovsky; A. A. Volobueva (Вестник рентгенологии и радиологии)
Objective: to evaluate pharmacoeconomic advantages of the application of magnetic resonance imaging (MRI) with hepatobiliary-specific contrast agent – gadoxetic acid in addition to contrast-enhanced computed tomography (CT) in the diagnosis of hepatocellular carcinoma (HCC).Material and methods. We performed the modeling and obtained the results of the pharmacoeconomic study: effectiveness analysis, cost analysis, and cost-effectiveness analysis. The cost analysis included only direct medical costs (the cost of contrast-enhanced CT, gadolinium-based contrast agent (GBCA) for MRI, and therapy per a patient with verified HCC diagnosis after diagnostic procedures). The financing was performed from the Compulsary Health Insurance Fund. The calculations were made per 1 patient.Results. The effectiveness analysis showed that the diagnostic scheme CT + MRI with gadoxetic acid was the most effective complex for the diagnosis of HCC because its application provided 50% of patients with 5-year overall survival (4.8 years), which was significantly higher than in patients who were diagnosed HCC with CT + MRI with extracellular GBCA (2.3 years) or CT (3.7 years). The cost-effectiveness analysis showed that the diagnostic scheme with gadoxetic acid was dominant because each disability-adjusted life year required fewer costs (14 862 rubles) in comparison with CT + MRI with extracellular GBCA (25 293 rubles) or CT (46 540 rubles). According to the results of the incremental cost-effectiveness ratio analysis, the application of the diagnostic complex with gadoxetic acid was characterized by the lowest rate of additional costs per 1 disability-adjusted life year.Conclusion. The pharmacoeconomic study showed that the application of MRI with a hepatospecific contrasting agent – gadoxetic acid in addition to contrast-enhanced CT was an effective and economically beneficial method of early HCC diagnosis.